CD4-CD8 lineage differentiation: Thpok-ing into the nucleus() - Wang, Lie (2009)
The mature αβ T cell population is divided into two main lineages defined by the mutually exclusive expression of CD4 and CD8 surface molecules (coreceptors), and differing in their MHC restriction and function. CD4 T cells are typically MHC II-restricted and helper (or regulatory) whereas CD8 T cells are typically cytotoxic. Several transcription factors are known to control the emergence of CD4 and CD8 lineages, including the zinc finger proteins Thpok and Gata3 which are required for CD4 lineage differentiation, and the Runx factors Runx1 and Runx3 which contribute to CD8 lineage differentiation. This review summarizes recent advances on the function of these transcription factors in lineage differentiation. We also discuss how the ‘circuitry’ connecting these factors could operate to match expression of lineage-committing factors Thpok and Runx3, and therefore lineage differentiation, to MHC specificity.